Electrodeposited carbon@Fe2O3 composites as binder-free anodes for lithium ion batteries. Issue 12 (1st December 2020) - Li, Hao; Yao, Chuan; Zhang, Sheng-Guo; Chao, Chun-Ying; Wei, Ji-Yu; Li, Dan
Abstract: Nanoscale metal oxides based binder-free electrodes have application prospects in the energy storage field. In this work, Fe2 O3 nanosheets composited with carbon matrix were prepared via the electrochemical deposition on the dopamine treated stainless steel substrate, followed by annealing treatment. The electrode delivers discharge capacity of 1242 mAh·g −1 at 600 mA·g −1 current density after 100 cycles. Furthermore, the electrode exhibited outstanding rate capability and its reversible capacity reaches to 960 mAh·g −1 at 1800 mA·g −1 current density. The properties of full-cells comprising LiFePO4 cathode were also studied. The improved cycle performance could be attributed to high electronic, ionic conductivity and strong tolerance to volume change benefited from the unique nanostructure and amorphous carbon structure. This work may provide a facile and efficient method for the synthesis of high performance Fe2 O3 anode materials.